Perineurioma of the Pancreas: A Rare Case - Saha, Sudipta; Jha, Ashesh; Mangal, Nidhi; Sharma, Naveen; Gupta, Sanjay; Agarwal, Sarla (JOP. Journal of the Pancreas, 2012)
Context Mesenchymal tumors of pancreas are rare. Case report We describe a case of perineurioma involving the body and tail of pancreas presenting as a slow growing abdominal lump. Conclusion Though perineurioma may arise from variety of anatomical sites including gastrointestinal tract, there is no previous report of perineurioma arising from the pancreas. Image: Intra-operative picture of pancreatic mass.